A moderated mediation model : intolerance of uncertainty, academic and prospective social life stress, anxiety and depressive symptoms, and perceived social support among university students during the COVID-19 pandemic - Meow, Emily Xin Yi (Nanyang Technological University, 2021)
It is crucial to investigate the psychosocial factors that contribute to or protect against the negative mental health and psychosocial problems among university students during the COVID-19 pandemic, when these problems may be heightened due to changes in academic learning and social interactions. This study examined domains of COVID-19 Stress as mediators of the relationship between Intolerance of Uncertainty and Anxiety-Depression Symptoms. It also investigated the moderating role of Perceived Social Support from Family and Friends. 200 participants across universities in Singapore filled in the COVIDStress Questionnaire, Patient Health Questionnaire-4, Intolerance of Uncertainty Scale-Short Form, and the Multidimensional Scale of Perceived Social Support. Results revealed a partial parallel mediation, where Academic Stress and Prospective Social Life Stress partially mediated the relationship between Intolerance of Uncertainty and Anxiety-Depression Symptoms. The positive correlation between Intolerance of Uncertainty and Prospective Social Life Stress uncovered an interesting possibility that university students may not be keen to return to their usual social lives. Perceived Social Support from Friends moderated the mediating effect of Prospective Social Life Stress, and the direct effect of Prospective Social Life Stress on Anxiety-Depression Symptoms, serving as a protective factor. Perceived Social Support from Friends moderated the direct effect of Academic Stress on Anxiety-Depression Symptoms where, interestingly, higher Perceived Social Support from Friends exacerbated this direct effect. Limitations, implications and future directions are discussed.